MENGAPA SANTRI ENGGAN MENCARI BANTUAN? MODEL LITERASI KESEHATAN MENTAL, STIGMA, DAN DUKUNGAN PENGASUH - Abdul karim; ahmad syamsul muarif; Nur Hafifah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
Santri may experience psychological distress but delay or avoid formal help. This integrative review develops a contextual model explaining how mental health literacy, stigma, and caregiver support shape help-seeking in Indonesian Islamic boarding schools. Thirty core publications published mainly between 2016 and 2026 were purposively synthesized through thematic comparison and mechanism mapping. The review shows that literacy improves problem recognition and knowledge of services, but knowledge alone does not ensure action. Public and self-stigma interrupt the translation of recognition into help-seeking, particularly when distress is interpreted as personal or religious weakness. Caregiver support provides legitimacy, confidentiality, emotional safety, access, and referral, thereby reducing stigma and strengthening the conversion of literacy into action. These findings generate the LSP-Santri Model, which positions caregiver support as a contextual bridge and buffering mechanism. The model offers a basis for future empirical testing and for designing pesantren-based, Islamic-integrated, tiered mental health services.